The Effect of Sports Drink Gel Treatment from Chia Seeds (Salvia hispanica L.) on the VO2 Max Capacity of Football and Futsal Players - Fauzi, Nur; Mardiana, Mardiana (Jurnal Gizi dan Pangan, 2022)
The purpose of this study was to determine the effect of sports energy gel drink from chia seeds (Salvia hispanica L.) on the VO2 max capacity of football and futsal players in Semarang. This is a quasi-experimental research using a crossover design on twenty-two (22) football and futsal players residing in Semarang, Indonesia. The duration of the study was five weeks, whereby 22 subjects in the control group were given 300 ml of mineral water added with butterfly pea extract as natural colorant, while another 22 subjects in the treatment group were given 300 ml of sports gel drink from chia seed 30 minutes before starting the exercise, twice a week. Data on weight, height, body fat percentage, energy and nutrient intake, and VO2 max capacity were collected. The results showed that there was a significant increase in the player's VO2 max capacity value after treatment with sports gel treatment (p=0.001), but there was no significant increase in the control group (p=0.314). Nutritional status, body fat percentages, physical activity, energy intakes, macro and micronutrients intake were found not to be correlated with VO2 max capacity. It can be concluded that administration of 300 ml sports gel drink from chia seeds before training increases the player's VO2 max capacity.